2017
DOI: 10.1002/col.22140
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of color information in the perception of icon‐type images

Abstract: Despite the ubiquity of icons in computing and mobile devices, the role of color in icon‐based interface design has yet to be fully elucidated. This study began by conducting a card sorting experiment to determine the importance of color in the perception of commercial icons, as opposed to the simpler icons typically used in a laboratory setting. The study also sought to ascertain the importance of color when considered alongside other visual attributes in the general perception of icons. Participants were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The analysis unveils a pivotal insight, highlighting the color scheme as the paramount attribute affecting elderly users' interaction with the ePHR interface components. This discovery resonates coherently with existing research conducted by Hsieh, T.J ( 89 ). Which accentuates the instrumental role of colors in cultivating visual appeal, an aspect imperative for seizing and sustaining users' attention.…”
Section: Discussionsupporting
confidence: 89%
“…The analysis unveils a pivotal insight, highlighting the color scheme as the paramount attribute affecting elderly users' interaction with the ePHR interface components. This discovery resonates coherently with existing research conducted by Hsieh, T.J ( 89 ). Which accentuates the instrumental role of colors in cultivating visual appeal, an aspect imperative for seizing and sustaining users' attention.…”
Section: Discussionsupporting
confidence: 89%
“…Also, icons are usually designed in single‐coloured in the first place and then edited their colour later, tailoring to the configuration of display devices [GSF01, ZKH*20]. Moreover, prior works found that icons' colouring is more critical to icons' visual attractiveness than effectiveness in the conveyance of meaning [Hsi17, CUG20, SZL*21]. Accordingly, we consider devising icons in single‐coloured is common in the design process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ]. Some researchers believe that EEG signals can be used to control and operate virtual home appliances [ 43 ], while others want to use EEG signals to investigate the impact of color on interface design [ 44 , 45 ], whilst others want to use EEG signals to analyze user aesthetic preferences in interface layout [ 46 , 47 ]. Therefore, studying user behavior during interface interaction using physiological data, such as eye movement data or EEG signals, can produce the best research results and design approaches.…”
Section: Introductionmentioning
confidence: 99%